(untitled) (Asian Journal of Current Engineering and Maths, 2013)
The objective of this paper is to study the radiation effect of Kuvshinshiki fluid on MHD free convection flow past a vertical porous plate with heat and mass transfer taking Visco-elastic and Darcy resistance terms into account and the constant permeability of the medium numerically and neglecting induced magnetic field in comparison to applied magnetic field. The velocity, temperature and concentration distributions are derived, discussed numerically. It is observed that velocity increases with increase in Gm, K and but it decreases with the increase in M andÎ» . It is observed that increase in Prandtl number Pr causes decreases in temperature. It is observed that increase in Schmidt number Sc leads to decreases in concentration. It is also noticed that skin friction increases with increase in K and but it decreases with the increase in R, M andÎ».